As características dos alunos são determinantes para o adoecimento de professores - um estudo comparativo sobre a incidência de Burnout em professores do ensino regular e especial - Silva, Nilson Rogério da [UNESP]; Almeida, Maria Amélia (FapUNIFESP (SciELO), 2011)
The practice of teaching is permeated by adverse working conditions, low wages, inadequacy of material and teaching resources, overcrowded classrooms, tension in relationships with the students, excessive work load, lack of safety in the school environment, insignificant participation in institutional planning and in institutional politics. The objective of the present study was to compare burnout among three groups of teachers who work in elementary grades: a) 20 teachers who teach in regular school classrooms without the inclusion of students with special educational needs - RSI Group; b) 20 teachers who teach in the regular classroom with special needs students - RCI Group; c) 20 teachers who teach in resource classrooms (SR Group). The instruments used for data collection were the Maslach Burnout Inventory -MBI. The data was analyzed by SPSS version 13.0 and Kruskal-Wallis test for comparison of the three groups. The results were organized in the form of figures and tables. In general, the results demonstrated that the groups presented relative similarity. The teachers from the SR Group obtained the best results in the evaluation of the three burnout scales when compared to the RSI Group and RCI Group, that is, there was a prevalence of answers in the lower levels of emotional exhaustion, high level of low personal accomplishment and low level for depersonalization. It is hoped that these results contribute to a better understanding of burnout in teachers from regular classrooms with or without students with educational special needs and/or to indicate new directions for investigation.
The student characteristics affect teachers' illnesses - A comparative study on the incidence of Burnout in regular and special education teachers
Keywords: Burnout; Elementary School Teachers; Regular Teaching; Special Education